Bring your own device readiness and productivity framework: a structured partial least square approach - Nik Rosli, Nik Nur Izzati; Mohamad Rosman, Mohamad Rahimi; Alias, Noor Rahmawati; Mohd Shukry, Amira Idayu; Razlan, Noor Masliana; Alimin, Noor Azreen (IAES International Journal of Artificial Intelligence (IJ-AI), 2025)
Bring your own device (BYOD) is defined as the practice that allow users to bring their private owned devices to organizations or institutions. BYOD bring benefits to both organizations and education sector in terms of cost efficient and productivity enhancement. However, there is a dearth of research on the determinant and impact of BYOD adoption in the context of educational sector. Therefore, the purpose of this study is to develop a BYOD readiness and impact framework based on four dimensions, namely technological readiness, individual readiness, contextual readiness, and organisational readiness. This study employed a quantitative research approach, utilizing an online survey questionnaire as the primary research instrument. Findings were analysed based on descriptive and inferential statistics using statistical package for social sciences (SPSS) version 26 and SmartPLS version 4.0. The findings shows that individual readiness, contextual readiness, and organisational readiness have a positive and significant relationship with BYOD adoption, while technological readiness proof to be an insignificant predictor. Subsequently, BYOD adoption also proven as a positive and significant predictor capable to improve user’s productivity.